Problem natury świadomości (Pokłosie 40 lat poszukiwań) = The nature of consciousness (40. years essence of the scientific investigations) - Szyszko-Bohusz, Andrzej (1934- ) (Zielona Góra: Uniwersytet Zielonogórski)
The author is an inventro of a new branch of pedagogy - The Holistic Pedagogy and The Hypothesis of Genetic Immortality- strictly connected with a holistic understanding of the nature of consciousness. He presents the multidisciplinary view on several fundamental notions, as life, consciousness, personal identity, heredity, genetic memory, etc. According to the above mentioned revision of to-date terminology is presented. The author claims the notion of heredity can be understood as contuinuity of the parents' lives in children.
Keywords: świadomość